Microplastics in Soil: Uncovering Their Hidden Chemical Implications - Tang, Kuok Ho Daniel (Tropical Aquatic and Soil Pollution, 2025)
This review synthesizes findings from over 100 recent studies to examine the multifaceted impacts of microplastics on soil health. Microplastics affect soil nutrient dynamics through mechanisms such as chemical leaching, nutrient adsorption, microbial shifts, and physical alterations in soil structure. Their influence varies by polymer type, particle morphology, concentration, and environmental conditions. While some microplastics may enhance nutrient retention, many contribute to nitrogen and phosphorus depletion, undermining soil fertility and agricultural productivity. Microplastics also modify soil pH in inconsistent ways, either increasing or decreasing it, thereby disrupting nutrient availability and microbial functions. The effects of microplastics on soil organic matter are equally complex. Biodegradable microplastics can stimulate microbial respiration and increase dissolved organic carbon, but they may also destabilize carbon pools, depending on the environmental context and soil conditions. Additionally, microplastics act as vectors or sinks for organic pollutants and heavy metals through diverse sorption–desorption mechanisms. Their interactions with contaminants such as pesticides, pharmaceuticals, and metals like lead, cadmium, and zinc are influenced by polymer type, surface aging, and coexisting soil constituents. Microplastics not only impair nutrient cycling but also alter microbial community composition, enzymatic activity, and pollutant degradation, raising concerns about the function of soil ecosystems and food safety. Future research should prioritize long-term, multi-factorial experiments under realistic environmental conditions. Key areas include disentangling the effects of conventional versus biodegradable microplastics, developing mechanistic models of pollutant interactions, and assessing the role of environmental parameters in mediating metal binding. Such efforts are vital for accurate risk assessments and informed mitigation strategies in terrestrial ecosystems.